High-hydrophobicity molecular catalyst as well as preparation method and application thereof
By introducing polytetrafluoroethylene into the cobalt phthalocyanine catalyst, a highly hydrophobic microenvironment is constructed, which solves the problems of reduced selectivity and hydrogen evolution reaction of the cobalt phthalocyanine catalyst under high current, achieves efficient CO2 reduction, and significantly improves CO2 efficiency. Faradaic efficiency and selectivity.
Patent Information
- Application Number
- CN202310887231.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The cobalt phthalocyanine catalyst cannot maintain high selectivity under high current, which is troubled by hydrogen evolution reaction and fails to effectively regulate the microscopic environment and interface CO2 concentration.
By introducing the hydrophobic agent polytetrafluoroethylene (PTFE), the hydrophobicity of the solid-supported cobalt phthalocyanine catalyst is improved, a microscopic hydrophobic environment is constructed, proton transfer is inhibited, the formation of the solid-liquid-gas three-phase contact interface is promoted, and the catalytic interface is improved CO2 concentration.
It suppresses the hydrogen evolution reaction at high current density, improves CO selectivity and Faradaic efficiency, reaching a CO Faradaic efficiency of 93%, and significantly reduces the cost of catalyst preparation.
Smart Images

Figure CN119332277A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis, and in particular, relates to a catalyst for electrocatalytic reduction of carbon dioxide to produce carbon monoxide, and a preparation method and application thereof. Background Art
[0002] The excessive consumption of traditional fossil fuels has led to an increase in the concentration of atmospheric carbon dioxide (CO2) year by year, causing a series of ecological and environmental problems such as the greenhouse effect (Zhu, DD, Liu, JL&Qiao, SZ Recent Advances in Inorganic Heterogeneous Electrocatalysts for Reduction of Carbon Dioxide. Adv. Mater. 28, 3423–3452 (2016)). Electrochemical CO2 reduction is a key technology to achieve carbon neutrality and close the carbon cycle pathway (Nam, D.-H. et al. Molecular Enhancement of Heterogeneous CO2 Reduction. Nat. Mater. 19, 266–276 (2020); Bushuyev, O S et al. What Should We Make with CO2 and How Can We Make It? Joule 2, 825–832 (2018); De Luna, P. et al. What would it Take for Renewably Powered Electrosynthesis to Displace Petrochemical Processes? Science 364, eaav3506 (An alkaline polymer electrolyte CO2 electrolyzeroperated with pure water-04-26)). Cobalt phthalocyanine (CoPc) has been widely used in the field of electrocatalytic CO2 reduction in recent years due to its advantages such as easy regulation of electronic structure, low loading and low cost (Ren, S. et al. Molecular Electrocatalysts Can Mediate Fast, Selective CO2 Reduction in a Flow Cell. Science 365, 367–369 (2019)). There are two main types of research on cobalt phthalocyanine catalysis: homogeneous and heterogeneous (Wu, Y., Liang, Y. & Wang, H. Heterogeneous Molecular Catalysts of Metal Phthalocyanines for Electrochemical CO2 Reduction Reactions. Acc. Chem. Res. 54, 3149–3159 (2021)).Compared with homogeneous catalysis in which catalyst molecules shuttle across the electrode surface (Sun, L., Reddu, V., Fisher, AC & Wang, X. Electrocatalytic Reduction of Carbon Dioxide: Opportunities with Heterogeneous Molecular Catalysts. Energy Environ. Sci. 13, 374–403 (2020)), heterogeneous catalysis has the advantages of fast electron transfer (Zhang, X. et al. Molecular Engineering of Dispersed Nickel Phthalocyanines on Carbon Nanotubes for Selective CO2 Reduction. Nat Energy 5, 684–692 (2020)) and high catalyst spatial density (Sathrum, AJ & Kubiak, CPKinetics and Limiting Current Densities of Homogeneous and Heterogeneous Electrocatalysts. J. Phys. Chem. Lett. 2, 2372–2379 (2011)) and low requirements for electrolyzers (Burdyny, T. & Smith, W. A. CO2 Reduction on Gas-Diffusion Electrodes and Why Catalytic Performance Must be Assessed at Commercially-Relevant Conditions. Energy Environ. Sci. 12, 1442–1453 (2019)).Immobilizing cobalt phthalocyanine on a carbon support is a commonly used heterogeneous catalytic strategy, which can exhibit nearly 100% carbon monoxide (CO) selectivity at low current (Marianov, AN & Jiang, Y. Mechanism-Driven Design of Heterogeneous Molecular Electrocatalysts for CO2 Reduction. Acc. Mater. Res. 3, 620–633 (2022); Sun, L. et al. Cobalt Quaterpyridine Complexes for Highly Efficient Heterogeneous CO2 Reduction in Aqueous Media. Advanced Energy Materials 12, 2202108 (2022); Zhang, X. et al. Highly Selective and Active CO2 Reduction Electrocatalysts Based on Cobalt Phthalocyanine / Carbon Nanotube Hybrid Structures. Nat Commun 8, 14675 (2017)).
[0003] It is not difficult to find that although the corresponding research has explored the ligands, carriers and catalytic pathways of the materials, no detailed research has been conducted on the micro-environment regulation to inhibit the occurrence of hydrogen evolution reaction at high current density. The inability of cobalt phthalocyanine catalysts to maintain high selectivity at high currents is still a key technical problem that needs to be solved. Summary of the invention
[0004] The present invention aims to solve the technical problems of regulating the microscopic hydrophobic environment of molecular catalyst cobalt phthalocyanine and controlling the CO2 concentration at the interface, and provides a method for preparing a highly hydrophobic molecular catalyst and its application. The method mainly introduces a hydrophobic agent polytetrafluoroethylene (PTFE) to improve the hydrophobicity of the immobilized cobalt phthalocyanine catalyst, construct a microscopic hydrophobic environment, inhibit proton transfer during the reaction, and promote the formation of a solid-liquid-gas three-phase contact interface, thereby increasing the CO2 concentration at the catalytic interface, inhibiting the hydrogen evolution reaction, and improving the CO Faraday efficiency, and can be well applied to the field of electrocatalytic CO2 reduction.
[0005] The technical purpose of the present invention is achieved through the following technical solutions.
[0006] A highly hydrophobic molecular catalyst, wherein the highly hydrophobic molecular catalyst is a cobalt phthalocyanine catalyst immobilized on granular polytetrafluoroethylene for hydrophobicity, and is prepared according to the following steps:
[0007] The carbon nanotubes hydrophobized by granular polytetrafluoroethylene and cobalt phthalocyanine are mixed in a mass ratio of 15:(1-3), N,N-dimethylformamide is added for acute ultrasonic dispersion, and the amount of N,N-dimethylformamide added is (20-30) ml per mg of cobalt phthalocyanine, centrifuged and the supernatant is removed, and after washing and drying, a highly hydrophobic molecular catalyst is obtained, wherein:
[0008] After polytetrafluoroethylene and carbon nanotubes are mixed, deionized water is added for dispersion to obtain a slurry material, which is allowed to stand and dry at room temperature to obtain carbon nanotubes hydrophobicized with granular polytetrafluoroethylene; after polytetrafluoroethylene and carbon nanotubes are mixed, the mass percentage of polytetrafluoroethylene is 10-30wt%.
[0009] Furthermore, after the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 20 wt %.
[0010] Furthermore, the mass ratio of the carbon nanotubes hydrophobized by granular polytetrafluoroethylene to cobalt phthalocyanine is 15:1.
[0011] Furthermore, the amount of N,N-dimethylformamide added is (20-25) ml per mg of cobalt phthalocyanine.
[0012] The invention discloses an application of the highly hydrophobic molecular catalyst in the electrocatalytic reduction of carbon dioxide to produce carbon monoxide.
[0013] When used, a highly hydrophobic molecular catalyst (i.e., the immobilized cobalt phthalocyanine catalyst of the present invention), FAA solution and DMF are mixed into a uniform solution, which is then sprayed on a gas diffusion electrode as a working electrode (i.e., a catalytic electrode) with a loading of 1-3 mg / cm 2 , using nickel foam loaded with iridium oxide as a counter electrode, power is applied to carry out an electrocatalytic reaction; the electrolyte used is an alkaline solution, such as a 1 mol / L KOH aqueous solution.
[0014] Compared with the prior art, the specific beneficial effects of the present invention are as follows:
[0015] (1) The PTFE-CoPc / CNT (i.e., a hydrophobic immobilized cobalt phthalocyanine catalyst using granular polytetrafluoroethylene) of the present invention constructs a microscopic hydrophobic environment for the catalyst cobalt phthalocyanine, which can inhibit proton mass transfer at a large current density, promote the increase of CO2 concentration at the active site, and inhibit the hydrogen evolution reaction. In addition, the constructed micron sheet structure has the function of intercepting CO2, promoting the formation of a gas-liquid-solid three-phase interface at the reaction interface, improving the selectivity of CO, and achieving a CO Faraday efficiency of 93%.
[0016] (2) The PTFE-CoPc / CNT preparation method of the present invention is simple, the reaction conditions are mild, the synthesis route is controllable and repeatable, no large-scale instruments and equipment are required, and it is economically feasible. At the same time, the prepared material has excellent performance in CO2 to CO production and has great industrial potential.
[0017] (3) The PTFE-CoPc / CNT of the present invention can be used as a highly efficient electrocatalytic CO2 reduction material to produce CO. It can maintain a high CO Faraday efficiency at high current density, and its selectivity is comparable to that of precious metal catalysts such as gold and silver. In addition, its loading amount is only one thousandth of that of metal catalysts such as gold and silver, which significantly reduces the cost of catalyst preparation, facilitates the commercialization of carbon dioxide to produce carbon monoxide, and provides technical support for the dual-carbon policy. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the synthesis route of the hydrophobic immobilized cobalt phthalocyanine on polytetrafluoroethylene obtained in Example 2.
[0019] Figure 2 This is the SEM characterization result of PTFE-CoPc / CNT obtained in Example 2.
[0020] Figure 3 This is the EDS characterization result diagram of PTFE-CoPc / CNT obtained in Example 2.
[0021] Figure 4 This is the XRD characterization result diagram of the cobalt phthalocyanine catalyst obtained in Example 1-2.
[0022] Figure 5 This is a cross-sectional SEM characterization result of the cobalt phthalocyanine catalytic electrode obtained in Example 3-4.
[0023] Figure 6 This is the CLSM characterization result of the cobalt phthalocyanine catalytic electrode obtained in Example 3-4.
[0024] Figure 7 This is a graph showing the contact angle test results of the cobalt phthalocyanine catalytic electrode obtained in Example 3-4.
[0025] Figure 8 This is a graph showing the results of the Faraday efficiency characterization of the CO2 reduction product CO obtained by the cobalt phthalocyanine catalytic electrode obtained in Example 3-4.
[0026] Fig. 9 This is a graph showing the local current density characterization results of the electrocatalytic CO2 reduction product CO obtained by the cobalt phthalocyanine catalytic electrode obtained in Example 3-4. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.
[0028] Example 1
[0029] Accurately weigh 15 mg of carbon nanotubes and 1 mg of cobalt phthalocyanine in a beaker, add 20 mL of N,N-dimethylformamide (DMF), ultrasonically treat for 30 min, centrifuge at 7000 r / min for 3 min, remove the supernatant, wash the obtained solid with DMF, ethanol and deionized water in turn, and dry in an oven at 80°C for 10 h to obtain immobilized cobalt phthalocyanine (CoPc / CNT).
[0030] Example 2
[0031] (1) Accurately weigh 20 mg of carbon nanotubes and spread them evenly in a beaker. Take 5.6 μL of PTFE emulsion (i.e., a suspended aqueous solution of PTFE) with a mass concentration of 0.9 g / mL and dilute it to 200 μL with deionized water. Add the diluted emulsion dropwise into the beaker and perform ultrasonication for 10 min to uniformly mix the emulsion and carbon nanotubes to form a slurry (the mass fraction of PTFE in the solid is 20 wt%, i.e., the mass of PTFE / the sum of the mass of PTFE and the mass of carbon nanotubes).
[0032] (2) The obtained slurry mixture was allowed to stand at room temperature of 20-30 degrees Celsius overnight (8 hours), and dried in an oven at 80 degrees Celsius for 10 hours to obtain PTFE-CNT (20 wt%).
[0033] (3) 15 mg of PTFE-CNT powder and 1 mg of cobalt phthalocyanine were mixed in a beaker, 20 mL of N,N-dimethylformamide (DMF) was added, and ultrasonic treatment was performed for 30 min. After centrifugation at 7000 r / min for 3 min, the supernatant was removed, and the obtained solid was washed with DMF, ethanol, and deionized water in sequence, and dried in an oven at 80 °C for 10 h to obtain PTFE-CoPc / CNT.
[0034] Figure 1 This is the synthesis route of the hydrophobic immobilized cobalt phthalocyanine on polytetrafluoroethylene obtained in Example 2. Figure 2 This is a scanning electron microscope image of the PTFE-CoPc / CNT obtained in Example 2, in which the PTFE presents a granular morphology. Figure 3 The energy spectrum of PTFE-CoPc / CNT obtained in Example 2 shows the aggregation distribution of F elements, that is, PTFE is polymerized. The X-ray diffraction characterization results of the cobalt phthalocyanine catalyst obtained in Example 1-2 are shown in Figure 4 As shown, Example 2 has an obvious diffraction peak at 2θ=18°, indicating that PTFE is successfully modified on CNT.
[0035] Example 3
[0036] 10 mg of the CoPc / CNT catalyst prepared in Example 1, 80 μL of FAA solution (purchased from Fuel Cell Store, with a mass percentage of 25 wt%), and 10 mL of DMF were mixed in a beaker and ultrasonicated for 30 min to form a uniform mixed solution. The mixed solution was sprayed onto a 2×2 cm 2 The gas diffusion electrode was weighed on an analytical balance before and after spraying to control the solid loading of the electrode to 1.5 mg / cm 2 .
[0037] Example 4
[0038] 10 mg of the PTFE-CoPc / CNT catalyst prepared in Example 2, 80 μL of FAA solution (purchased from Fuel CellStore, with a mass percentage of 25 wt%), and 10 mL of DMF were mixed in a beaker and ultrasonicated for 30 min to form a uniform mixed solution. Using nitrogen as the carrier gas, the mixed solution was sprayed onto a 2×2 cm 2 The gas diffusion electrode was weighed on an analytical balance before and after spraying to control the solid loading of the electrode to 1.5 mg / cm 2 .
[0039] Figure 5 The cross-sectional SEM characterization results of the catalytic electrodes prepared in Examples 3-4 can be used to obtain the thickness and structure of the catalytic electrodes. The thickness of Example 4 is greater than that of Example 3. Figure 6 The laser confocal scanning electron microscope characterization image of the catalytic electrode prepared in Example 3-4 shows that the fluorescence intensity of Example 4 decays slowly, indicating that the degree of formation of the gas-liquid-solid three-phase interface is high. Reference Shi, R. et al. Efficient Wettability-Controlled Electroreduction of CO2 to CO at Au / C Interfaces. Nat Commun 11, 3028 (2020). The contact angle test experimental results of the catalytic electrode obtained in the above Examples 3-4 are as follows Figure 7 As shown, the contact angles of Examples 3-4 increase successively, indicating that the modification of PTFE significantly improves the hydrophobicity of the catalyst.
[0040] Example 5
[0041] The performance of the catalytic electrode was tested using a membrane electrode reactor. The membrane electrode reactor used was referenced by Zhang, G. et al. Efficient CO2 Electroreduction on Facet-Selective Copper Films with High Conversion Rate. Nat Commun 12, 5745 (2021). The test electrolyte was an aqueous solution of 1 mol / L KOH, and the electrode area was 4 cm 2 , the product enters the gas chromatography for detection.
[0042] The CO Faraday efficiency values of the catalytic electrodes prepared in Examples 3-4 at different test current densities are as follows: Figure 8 As shown, it can be seen that the performance of PTFE-CoPc / CNT is significantly better than that of CoPc / CNT, that is, the improvement of hydrophobicity inhibits proton transport, increases the CO2 concentration at the reaction interface, and maintains a high reaction selectivity at a high current density. The local current density of CO in the catalytic electrode prepared in Example 3-4 at different test current densities is shown in Figure 3. Fig. 9 As shown, it can be seen that its rules are Figure 8 Similarly, the local current density of PTFE-CoPc / CNT is significantly higher than that of CoPc / CNT.
[0043] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.
Claims
1. A highly hydrophobic molecular catalyst, characterized in that: The highly hydrophobic molecular catalyst is a cobalt phthalocyanine catalyst immobilized on granular polytetrafluoroethylene for hydrophobicity, and is prepared according to the following steps: The carbon nanotubes hydrophobized by granular polytetrafluoroethylene are mixed with cobalt phthalocyanine in a mass ratio of 15:(1-3), N,N-dimethylformamide is added for acute ultrasonic dispersion, the amount of N,N-dimethylformamide added is (20-30) ml per mg of cobalt phthalocyanine, centrifuged and the supernatant is removed, and the mixture is washed and dried to obtain a highly hydrophobic molecular catalyst, wherein: after the polytetrafluoroethylene and the carbon nanotubes are mixed, deionized water is added for dispersion to obtain a slurry-like material, and after standing and drying at room temperature, the carbon nanotubes hydrophobized by granular polytetrafluoroethylene are obtained; after the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 10-30wt%.
2. A highly hydrophobic molecular catalyst according to claim 1, characterized in that: After the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 20 wt %.
3. A highly hydrophobic molecular catalyst according to claim 1, characterized in that: The mass ratio of carbon nanotubes hydrophobized by granular polytetrafluoroethylene to cobalt phthalocyanine is 15:
1.
4. A highly hydrophobic molecular catalyst according to claim 1, characterized in that: The amount of N,N-dimethylformamide added is (20-25) ml per mg of cobalt phthalocyanine.
5. A method for preparing a highly hydrophobic molecular catalyst, characterized in that: The highly hydrophobic molecular catalyst is a cobalt phthalocyanine catalyst immobilized on granular polytetrafluoroethylene for hydrophobicity, and is prepared according to the following steps: The carbon nanotubes hydrophobized by granular polytetrafluoroethylene are mixed with cobalt phthalocyanine in a mass ratio of 15:(1-3), N,N-dimethylformamide is added for acute ultrasonic dispersion, the amount of N,N-dimethylformamide added is (20-30) ml per mg of cobalt phthalocyanine, centrifuged and the supernatant is removed, and the mixture is washed and dried to obtain a highly hydrophobic molecular catalyst, wherein: after the polytetrafluoroethylene and the carbon nanotubes are mixed, deionized water is added for dispersion to obtain a slurry-like material, and after standing and drying at room temperature, the carbon nanotubes hydrophobized by granular polytetrafluoroethylene are obtained; after the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 10-30wt%.
6. The method for preparing a highly hydrophobic molecular catalyst according to claim 5, characterized in that: After the polytetrafluoroethylene and the carbon nanotubes are mixed, the mass percentage of the polytetrafluoroethylene is 20 wt %.
7. The method for preparing a highly hydrophobic molecular catalyst according to claim 5, characterized in that: The mass ratio of carbon nanotubes hydrophobized by granular polytetrafluoroethylene to cobalt phthalocyanine is 15:
1.
8. The method for preparing a highly hydrophobic molecular catalyst according to claim 5, characterized in that: The amount of N,N-dimethylformamide added is (20-25) ml per mg of cobalt phthalocyanine.
9. Use of a highly hydrophobic molecular catalyst as claimed in any one of claims 1 to 4 in the electrocatalytic reduction of carbon dioxide to produce carbon monoxide.
10. Use of a highly hydrophobic molecular catalyst according to claim 9 in electrocatalytic reduction of carbon dioxide to produce carbon monoxide, characterized in that: When in use, highly hydrophobic molecular catalyst, FAA solution and DMF are mixed into a uniform solution and sprayed on the gas diffusion electrode as the working electrode (i.e., catalytic electrode) with a loading of 1-3 mg / cm 2 , using nickel foam loaded with iridium oxide as a counter electrode, power is applied to carry out an electrocatalytic reaction; the electrolyte used is an alkaline solution, such as a 1 mol / L KOH aqueous solution.
Citation Information
Patent Citations
Method for preparing heterogeneous monomolecular electrocatalyst from metal phthalocyanine molecule-nanocarbon and application of heterogeneous monomolecular electrocatalyst
CN110911694A
Preparation method and application of composite cathode integrating efficient in-situ electrosynthesis of hydrogen peroxide and catalytic performance
CN112479317A
Gas diffusion electrode for preparing carbon monoxide by electrolyzing carbon dioxide and preparation method of gas diffusion electrode
CN113445064A
Preparation method and application of asymmetric coordination monatomic catalyst
CN114086212A
Cobalt phthalocyanine-amino carbon nanotube catalyst as well as preparation method and application thereof
CN115652364A